The Jurisprudent Qabisa ben Thuaib Al-Khuza’i - The Advisor of Caliph Abdul-Malek- His Life, Biography Political and Administrative role in the Umayyad Era - Ahmed, Arabiya Qassim (Al-Adab Journal, 2015)
This paper tackles the biography of the jurisprudent Qabisa ben Thuaib Al-Khuza’i. He was born in a religious environment and was raised by the Prophet (pbuh) after he has lost his father. Then, he was raised in a religious milieu and took his knowledge from the companions and the followers and the narrators of hadith. He took from them many references. Then he moved to the Levant (Al-shaam) and started a new journey in life. He was the preferred for the Caliph Abdul-Malek ben Marwan 65-86 A.H./684-705 AC due to his animate relationship between them since they were both in Medina and they met often for knowledge. In addition to that, Qabisa ben Thuaib Al-Khuza’i was honest and courageous and wise. All these features made the caliph call for Qabisa to assume many positions like the penman in the divan for seal and letters. He was like a minister and an advisor to the Caliph.